Phylogenetic study of Genus Scomberomorus based on cyt b gene in the north and south coast of Java, Indonesia - Purba, Laurentia Henrieta Permita Sari; Sutan, Ditha Klarissa; Simanjuntak, Monayanti; Kusumaningrum, Fransisca Victory (JSMARTech, 2025)
Indonesia possessed megabiodiversity especially in marine animals. As the highly commercial commodities, the understanding for species distribution of Spanish mackerel and seerfish (Scomberomorus spp.) plays a key role for their sustainability. Thus, the aim of this study was to map the species distribution of Scomberomorus spp. in Java surrounding waters. We collected 10 specimens from 4 landing sites in northern and southern coast of Java. Using partial cytochrome b gene fragment ( 400 bp), we characterized the gene and haplotype diversity as well as the phylogenetic relationship. Three species of mackerel and seerfish were found in Java coastal line. The genetic differences Scomberomorus sp. ranged from 0 to 14%. By this study, we provide useful data that can be utilized as biodiversity monitoring. In addition, we confirmed that cythocrome b were effective for future application in fishery management and product authentication of mackerel in Java and surrounding areas.